Role Conflict and Well-Being of Working Mothers - Nona, Elonora Helen Agyo Pasca; Sumargi, Agnes Maria; Ratna, Josephine Maria Julianti (Psychopreneur Journal, 2022)
Abstract. Working mothers bear a heavy burden during the COVID-19 pandemic because they have to divide their time and energy to take care of the household, including their children, and carry out their work at the same time. This makes working mothers vulnerable to role conflicts. Problems at home can be carried over to the workplace (Family-to-Work Conflict, FWC) and problems at work can be carried over to their homes (Work-to-Family Conflict, WFC), thus affecting the well-being of mothers. This study aimed to investigate the relationship between role conflicts and well-being of working mothers. Participants were 44 working mothers who worked full-time, had children aged 2-6 years, and lived in Surabaya. They completed online questionnaires, the Work-Family Conflict Scale and the Pemberton Happiness Index. Based on correlational analysis with Kendall’s tau b, it was found that there was a significant relationship between FWC and maternal well-being, but the relationship between WFC and maternal well-being was not significant. This shows that role conflict, particularly family-to-work conflict, have an impact on decreasing maternal well-being.